Noninvasive, Wearable, Pulsed Shortwave (Radiofrequency) Therapy for Analgesia following Knee and Hip Arthroplasty: A Case Series - Said, Engy T; IV, John J Finneran; Gabriel, Rodney A; Sztain, Jacklynn F; Ball, Scott T; Cidambi, Krishna R; Abdullah, Baharin; Ilfeld, Brian M (Archives of Clinical and Medical Case Reports, 2022)
Background: Minimizing pain and opioid requirements following major orthopedic surgery can be challenging. Nonthermal, pulsed, shortwave (radiofrequency) therapy is a noninvasive treatment described previously as a possible analgesic modality following minor surgical procedures. The devices may be applied in a few minutes or less, are simply taped in place over the area of pain, are less expensive than a large bottle of acetaminophen, function for 30 days without any required intervention, may be applied to any part of the body, and produce no side effects-patients cannot detect any sensations from the devices-or substantial risks. Here we present a case series to explore the use of pulsed shortwave therapy for major joint arthroplasty. Case Report: Following unilateral total knee (n=2) and hip (n=5) arthroplasty, patients had 1-2 noninvasive, wearable, disposable, pulsed shortwave devices (Model 088, BioElectronics, Frederick, Maryland) affixed over the surgical incision (functioning continuously for 30 days). Average daily pain at rest and with movement was a median of 0-4 as measured using a 0-10 numeric rating scale for the entire follow-up period. Maximum pain each day was a median of 5 and 6 for the first two days, respectively, and over the subsequent weeks fell to 0 by Day 35. Three patients avoided opioid use entirely, while the remaining individuals required 0-7.5 mg of oxycodone daily. No device-related localized irritation, side effects, or complications were identified. Conclusions: Pulsed shortwave devices may be an effective analgesic, possibly obviating opioid requirements in some cases following knee and hip arthroplasty.